Effectiveness of different solvent-modulated Traditional Chinese Medicine applied to Shenque(RN8) in the treatment of constipation (不同溶剂调制药物贴敷神阙穴治疗便秘的效果观察) - ZHANG Li (张莉); SHEN Juan (沈娟); PAN Lei (潘磊); ZHANG Yuanyuan (张园园); LI Yuye (李玉叶); DI Yanhui (邸延辉); ZHOU Xiaoyan (周晓艳) (Association of Integrative Nursing, 2021)
Objective The aim of this study is to explore the clinical effect of applying Traditional Chinese Medicine prepared with different solvents to Shenque(RN8) acupoint for the treatment of constipation. Methods A total of 60 patients with constipation during their hospital stay between Mary 2020 and Mary 2021 were included and randomly assigned into control group and treatment group, with 30 cases in each group. The control group and treatment group received the therapy of applying the TCM drugs prepared with warm water and rice wine respectively to Shenque(RN8) acupoint for 4 h once a day and there were two rounds of treatment, with each round lasting 7days. Results The total effective rate of treatment group and control group was 96. 67% and 73. 33% respectively and there was statistically significant difference between the two groups (P＜0. 05). Conclusion Application of the TCM drugs prepared with rice wine to Shenque(RN8) acupoint for the treatment of patients with constipation during their hospital stay is clinically effective and safe and it can be promoted to use in clinical nursing. (目的 探讨不同溶剂调制药物贴敷神阙穴治疗便秘的临床疗效。方法 选取2020年5月-2021年5月北京中医药大学东方医院心内科住院期间合并便秘患者, 共选择病例60例, 按照随机对照法分为对照组和治疗组, 各30例。对照组给予温水调和中药剂贴敷治疗, 治疗组给予黄酒调和中药剂贴敷治疗, 分别给予神阙穴贴敷4 h, 1次/d, 7 d为1个疗程, 共治疗2个疗程。 根据症状改善情况评价干预效果。结果 治疗组总有效率为96. 67%(29/30), 对照组总有效率为73. 33%(22/30), 2组差异有统计学意义(P＜0. 05)。结论 采用黄酒调和中药剂贴敷神阙穴治疗住院期间便秘患者的临床疗效较好, 安全性良好, 可以在临床护理中推广使用。)